Clinical Outcomes of Intravitreal Preservative-Free Triamcinolone Preparation (Triesence®) for Cystoid Macular Oedema and Inflammation in Patients with Uveitis. (3rd October 2018) - Steeples, Laura R.; Anand, Nitin; Moraji, Jiten; Jones, Nicholas P.
ABSTRACT: Purpose : To assess the outcomes of intravitreal benzyl alcohol-free triamcinolone acetonide suspension in uveitis-related macular oedema. Methods : Single-center retrospective cohort study of 66 injections to 44 eyes of 40 patients. Uveitis diagnosis, systemic and local therapy, intraocular pressure (IOP), central retinal thickness (CRT), number of injections, time to re-injection and side-effects were noted during 6-months minimum follow-up. Results : Sixty eight percent of eyes received a single injection. 18% required 2 injections, and 13% received ≥3 injections with mean time to second and third injections of 25.5 and 52.7 weeks, respectively. 90% of injections were unilateral. Mean CRT reduced, and by 12-weeks visual acuity improvement >0.3logMar was achieved in 46%. Cataract progression (47%) and IOP>21 mmHg (45%) were the commonest adverse events. Conclusion : Preservative-free triamcinolone is an additional option for uveitis-related macular oedema, particularly in unilateral cases, with favorable CRT and visual outcomes. Repeat injections may be necessary, and the period of efficacy varies between eyes.